PENGEMBANGAN BUKU AJAR IPS SD UNTUK MENINGKATKAN KUALITAS PERKULIAHAN PADA MAHASISWA S1 PGSD FIP UNESA - Waspodo Tjipto Subroto, ; Suprayitno, (Pendidikan Sekolah Dasar, 2011)
Education  of  Social Studies  is  one  subject which shall be program the students of S1 PGSD Unesa FIP. As one of the subject areas of study, Education of social studies  aims to further students understanding and skills in applying learning strategies social studies in Primary Schools. This  development   objective  is  to  develop  courses   Textbook  Education  of  Social Studies at  the Department  of S1 PGSD Unesa FIP and learning tools in the   form outlined by Course Plan (GBRP) following Lectures Events Unit (SAP)  for one semester.    Development  of the textbook   is   specified  with include:  describing  the  feasibility  of   the substantive, level of difficulty, the level of legibility, and effectiveness of the IPS Education Textbook Advanced Class  at the Departmentof S1 PGSD FIP Unesa.  Shape   product   development   Textbook   Education  of  Social Studies course consists of lectures and educational material outlined plans Lectures, Lectures  and  Events Unit. This research includes development research with model 4D (four-D) which according to Thiagarajan (1974) more detailed and systematic.   The research was conducted on students S1 PGSD FIP Unesa, Force 2008. Collecting data using instruments questionnaires, observation sheets and test results of learning. The data were analyzed using qualitative descriptive analysis technique. Deskripstif analysis is used to present data from user questionnaire results textbook, study and documentation of test results collected student work portfolios of learning social studies education. The result of  the  development    Textbook Education  of  Social Studies showed quite effective  role  in improving the quality of lectures on elementary social studies education courses  Advanced Class.   Similarly,   student   responses  to learning device Textbook quite positive.  While  the  response lecturers subjects developed textbook assume  could  be  one of   reference for elementary social studies education courses Advanced Class. About the constraints   faced  in understanding the  Education  of  Social Studies Elementary Textbook Advanced Class, students  generally  expressed  no  problems were significant. As a suggestion which could be put forward in the development of this learning tool, students who take courses Education  of  Social Studies Information should read this textbook as a reference.